Particulate organics degradation and sludge minimization in aerobic, complete SRT bioreactors. (1st May 2016) - Amanatidou, Elisavet; Samiotis, Georgios; Trikoilidou, Eleni; Tsikritzis, Lazaros
Abstract: The study evaluates the assumption that in activated sludge processes and under specific operating conditions, the considered unbiodegradable particulate organic fractions of influent (XU ) organic solids and biomass decay residues (cell debris, XE ) are degraded. The evaluation was performed by comparing sludge observed yield ( Y obs ) evolution in two full scale, complete solids retention time ( SRT ), aerobic bioreactors, to the predictions of two activated sludge models. The results showed that in steady state operating conditions of complete solids retention AS processes very low solids accumulation occur. In these conditions, solids accumulation is slightly affected by kinetic coefficients and significantly affected by XU and XE degradation rates. High endogenous residues degradation rate values of 0.05 d −1 and 0.02 d −1 were estimated for the two bioreactors, resulting in low solids accumulation, calculated at 1.6 tons and 3.59 tons per year respectively, of which 1.37 and 0.87 tons were non volatile suspended solids. Depending on WWTP operating conditions the endogenous residues degradation rate is the limiting factor of solids accumulation and consequently for particulate organics degradation. Graphical abstract: Highlights: Particulate organic matter under specific operational conditions is degradable. Complete SRT AS aerobic process leads to negligible solids accumulation. Endogenous residues degradation rate ( b XE) is solids accumulation limiting factor. High MLVSS, HRT and SRT AS processes, have lower Y obs and higher b XE values. High b XE values result in low Y obs and thus in lower solids accumulation.